Content of vol. 29, 2025, Journal Scientific and Applied Research: Content of vol. 29, 2025, Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Content of vol. 29, 2025, Journal Scientific and Applied Research